ANALISIS FAKTOR SOSIAL DAN EKONOMI TERHADAP PENGGUNAAN ALAT KONTRASEPSI PADA PUS DI DENPASAR SELATAN - Candamayanti, Ni Made Maya; Karmini, Ni Luh (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.03.TAHUN.2024, 2024)
The purpose of this study was to analyze the effect of age, education level, accessibility of information on family planning services, income and family support simultaneously and partially on the use of contraceptives in PUS in South Denpasar. This research was conducted in South Denpasar sub-district. The samples taken 100 couples of childbearing aged 20-49 years with married status in South Denpasar. Data was collected by observation method using a questionnaire then analyzed logistic regression. The results of the study can be concluded that age, education level, accessibility of information on family planning services, income and family support simultaneously influence the use of contraceptives in PUS in South Denpasar. Partially, age, education level, accessibility of information on family planning services, income and family support have a positive and significant effect on the use of contraceptives in PUS in South Denpasar.